(untitled) (Journal of actual problems of jurisprudence, 2019)
In this article the analysis of reforming of system of public administration in the field of health care of Kazakhstan on the basis of research of the constitutional and special legislation is considered. The analysis of current trends of reforming in the field in the light of Strategy realization Kazakhstan – 2050 is carried out. Keywords: health, finance, national health care system, medical education.